2016
DOI: 10.1097/ta.0000000000000940
|View full text |Cite
|
Sign up to set email alerts
|

Extending the golden hour

Abstract: In the setting of severe ongoing hemorrhage, P-REBOA increased survival time beyond the golden hour while maintaining cMAP and carotid flow at physiologic levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(69 citation statements)
references
References 20 publications
1
66
1
1
Order By: Relevance
“…Some studies reported that small introducer sheaths for REBOA may be associated with fewer complications [27, 29] and that ultrasound should be optimized for REBOA [30]. Moreover, partial or intermittent REBOA should be considered in some cases [31, 32]. However, their effect remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that small introducer sheaths for REBOA may be associated with fewer complications [27, 29] and that ultrasound should be optimized for REBOA [30]. Moreover, partial or intermittent REBOA should be considered in some cases [31, 32]. However, their effect remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…1418 However, the techniques of partial REBOA (P-REBOA) and intermittent REBOA (I-REBOA) using existing technology pose a risk of ongoing hemorrhage. 17, 19 Studies with large animal injury models have demonstrated that P-REBOA can lead to increased blood loss when compared to complete REBOA. 17 Furthermore, hemodynamic instability during attempts at partial flow restoration has been observed in early clinical experience.…”
Section: Introductionmentioning
confidence: 99%
“…17, 19 Studies with large animal injury models have demonstrated that P-REBOA can lead to increased blood loss when compared to complete REBOA. 17 Furthermore, hemodynamic instability during attempts at partial flow restoration has been observed in early clinical experience. 20 While this approach to aortic flow reintroduction is rational in resource-rich environments with access to blood products and operating rooms, it will be limited in scenarios in which a prolonged time period exists between injury and hemorrhage control.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing a rapidly fatal porcine liver injury model, P-REBOA was able to extend survival nearly 3.5-fold over no intervention, but was unable to achieve satisfactory hemostasis over complete REBOA. Further translational investigation suggests that (15). P-REBOA may best be implemented following a brief period of complete aortic occlusion to achieve initial hemostasis prior to the re-introduction of distal blood flow.…”
Section: Endovascular Methods For Achieving Aortic Occlusionmentioning
confidence: 99%
“…The dysregulation of the immune response in animal models of aortic occlusion leads to migration of leukocytes into ischemic distal tissue beds, principally the intestines, and profound leukopenia (9, 15). Similar leukocyte sequestration in the intestines of humans is associated with mesenteric ischemia, intestinal dysfunction, and an increased risk of sepsis (16).…”
Section: Effects Of Aortic Occlusionmentioning
confidence: 99%